1998
DOI: 10.1002/ana.410440403
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy with HSP72 is neuroprotective in rat models of stroke and epilepsy

Abstract: Brain areas damaged by stroke and seizures express high levels of the 72-kd heat shock protein (HSP72). Whether HSP72 represents merely a marker of stress or plays a role in improving neuron survival in these cases has been debated. Some induced tolerance experiments have provided correlative evidence for a neuroprotective effect, and others have documented neuroprotection in the absence of HSP72 synthesis. We report that gene transfer therapy with defective herpes simplex virus vectors overexpressing hsp72 im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
194
5
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(213 citation statements)
references
References 51 publications
11
194
5
3
Order By: Relevance
“…Infarct volumes obtained with our procedure are very similar to those found with longer periods of ischemia [13,51,76]. Several studies have also found large infarct areas using only 1 h of transient focal ischemia and have used this model to investigate the effects of different compounds in experimental ischemic stroke in the rat [58,67,74,80]. Since nimesulide's neuroprotection could easily result from drug-induced hypothermia rather than a specific pharmacological effect, we strictly monitored rectal temperature and found that nimesulide did not modify this physiological variable (data not shown).…”
Section: Procedures For Transient Middle Cerebral Artery Occlusion (Msupporting
confidence: 73%
See 1 more Smart Citation
“…Infarct volumes obtained with our procedure are very similar to those found with longer periods of ischemia [13,51,76]. Several studies have also found large infarct areas using only 1 h of transient focal ischemia and have used this model to investigate the effects of different compounds in experimental ischemic stroke in the rat [58,67,74,80]. Since nimesulide's neuroprotection could easily result from drug-induced hypothermia rather than a specific pharmacological effect, we strictly monitored rectal temperature and found that nimesulide did not modify this physiological variable (data not shown).…”
Section: Procedures For Transient Middle Cerebral Artery Occlusion (Msupporting
confidence: 73%
“…Other therapeutic strategies for stroke include hypothermia [20,65,81], antioxidants [7,13,14,64], blockade of excessive synaptic Zn 2+ release [75], antiapoptotic strategies [26,53], administration of growth factors [1,40], erythropoietin [67], recombinant human interleukin-1 receptor antagonist [47], statins [73], gene therapy [80,81] and approaches involving transfer of new cells, such as stem cells, and neuronal precursors cells [1,46,63].…”
Section: Introductionmentioning
confidence: 99%
“…199 Expression of 72-kDa heat shock protein via HSV vector also improved neuron survival against transient focal ischemia. 200 Ad vectors have also been shown effectively to transfer genes to cerebral blood vessels and overlying meninges, 201 and transfer of genes for enzymes with vasodilator function may also attenuate ischemic damage. Ex vivo therapy for ischemia includes transplantation of fibroblasts genetically modified to secrete NGF into the hippocampus, which protected neurons within CA1 and CA2 regions from damage.…”
Section: Ischemiamentioning
confidence: 99%
“…Exploratory modalities have included: delivery of heat shock protein (HSP72) via an HSV amplicon vector which protect hippocampal neurons from kainic acid toxicity; 200 Ad-mediated delivery of glutamic acid decarboxylase to increase synthesis of the inhibitory neurotransmitter GABA; 240 and lipofectin-mediated delivery of cholecystokinin, an anticonvulsant and anti-opioid neuropeptide, to the ventricles to alleviate (temporarily) audiogenic seizures. 241 Endocrine functions Viral vectors have also been used as tools for examining the role of hormonal replacement therapy in distinct neuroendocrine and/or sensory pathways.…”
Section: Epilepsymentioning
confidence: 99%
“…Although as yet undeveloped as a gene therapy target it would be wise to concurrently design and evaluate vectors capable of transduction of the desired substrate. [5][6][7] Arteriovenous malformations (AVMs) represent another potentially novel target for CNS gene therapy. These lesions, reflecting dysgenesis of the vasculature, have the proclivity to bleed and produce morbidity (including seizures) and death.…”
Section: Novel Targets For Cns Gene Therapymentioning
confidence: 99%